(St)aging in place: Information and communication technologies for a health-centered agile dwelling unit - Cevallos, Nicole; Ramadhani, Widya A.; Lindgren, Julia; Bell, Bradley; Martinez-Cosio, Maria; Harvey, Thomas E.; Nanda, Upali; Mustata Wilson, Gabriela (Frontiers in Public Health, 2023)
As the number of older adults is growing rapidly in the U.S., the need for personalized, innovative, and sustainable Information and Communication Technologies (ICTs) solutions is critical to support individuals' social, emotional, and physical health. Such technology can significantly help older adults’ ability to live independently in their homes despite the challenges the aging process may present, referred to as aging or staging in place. In this study, we explored ways to integrate ICTs into Agile Dwelling Units (AgDUs) through affordable, innovative, technology-enabled tools and practices that can be adapted to respond to individual’s needs while supporting independent, secure, and engaged healthy living. The technology-enabled and human-centered AgDUs organically transform in response to users' needs. This approach offers a viable solution for older adults at different stages throughout their lifespan to transition into an intimate, technologically-enhanced living environment while allowing for (1) customization to user's needs; (2) cost optimization and maintenance; and (3) accessibility that minimizes gaps in compliance from a provider and user perspectives. Integrating ICTs in AgDUs to support health monitoring and management could reduce forthcoming pressure on the healthcare system and care providers to accommodate the needs of older adults. This approach is described through a collaborative multidisciplinary lens that highlights a partnership between academia, industry experts, and key stakeholders to advance healthy living and extend lifespan through design-build and technology integration. The main goal of this approach is to increase access to health services and optimize healthcare costs.